PENDIDIKAN BERKARAKTER ISLAMI BAGI ANAK YATIM - Abdurrahman Misno Bambang Prawiro (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2015)
Education is the right of every citizen of Indonesia, so that the government must provide greater opportunities for people to be able to obtain quality education. 1945 opening paragraph 4 states that the State is aimed intellectual life of the nation. The effectiveness of a learning process in general determined by the curriculum and education system applied to the educational environment, with regard to education that is applied to the orphans it is necessary to be able to answer specific curriculum and accommodate the needs of an orphan, both physically and spiritually. This research was conducted in Pesantren Orphans Ibn Taymiyyah Bogor with audience santri orphan from the level of Madrasah Ibtidaiyyah (MI), MTs (MTs) and Madrasah Aliyah (MA). The psychology of orphans feel lost with his death one of their parents is a father. Results from this study showed that the loss of a father figure in their lives lead them to feel less protected so that their personalities tend to be more free. There needs to be a model of education that direct and guide them to become self-sufficient human well during the learning process or the results of the study. Islamic character education that provide learning patterns that are tailored to the age and maturity level of the spiritual into something that should be there for their education.